Un incitamento alla rivolta - Plätze des Protests in Venedig. Kontroversen um den Ausverkauf der Stadt. - (:unkn) unknown (Deutsches Institut für Urbanistik, 2019)
The article focuses on selected examples of protest in the public urban space of Venice. The city's imbalanced situation in terms of economy, society and culture has driven its inhabitants to the streets and squares in increasing numbers over the last two decades. The town hall is one of the meeting points for demonstrations, but there is no clearly defined place of encounter. Political manifestations take place at various symbolic and strategic locations in the city, and not only for topographical reasons. The example of the lagoon city illustrates how urban topography and architecture shape the communication processes of the inhabitants, influence their appropriation of places of political relevance, and lead the actors to create new physical and virtual spaces of action.
Keywords: Italien; Venedig; Kommunalpolitik; Stadtplatz; Historischer Platz; Öffentlicher Raum; Geschichte; Protest; Widerstand; Tourismus